Physical properties and fiber dimension in Stem, Branch and root of Alder Wood - Moya-Roque, Róger; Kiaei, Majid (Parlar Scientific Publications, 2015)
The aim of this study was to determine physical properties and fiber dimensions in stem, branch and root wood for alder (Alnus glutinosa L) species. For this purpose, three normal alder trees were selected from Khanican forest in north of Iran. Disks were taken from three parts such as stem, branch and root of trees. Testing samples were randomly taken at disk surfaces to examine the physical properties (according to the ISO standard for oven-dry density and volumetric shrinkage) and fiber dimension (fiber length, fiber diameter and lumen diameter according to the Franklin method). Analysis of variance (ANOVA) indicated that the wood samples had significant difference on the wood density, volumetric shrinkage, fiber length, fiber diameter and lumen diameter. The highest wood density, volumetric shrinkage and fiber length was found in stem wood, whereas root wood had a lighter density, larger fiber diameter and larger fiber lumen diameter. The branch wood had the lowest fiber dimensions (fiber length, fiber diameter and lumen diameter) compared to other wood sample parts. The relationship between wood density and volumetric shrinkage were determined by regression model. These relationships in root wood were very weaker compared to stem wood and branch wood.
Keywords: Madera; Fibras; Árboles maderables; Raíces; Ramas; Tallos; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Product science::Wood fibre and forest products